Comparison Sitagliptin/Metformin combination therapy with metformin monotherapy in patients with type 2 diabetes mellitus - زيدان ريم; ربا سلمان; ربا حمدان (Latakia University Journal -Medical Sciences Series, 2022)
Background: Type 2 diabetes mellitus(T2DM) is considered as an important cause of morbidity worldwide due to the increased risk for microvascular complications leading to poor outcome. Early initiation of sitagliptin with metformin might improve the final outcome of patients. Aim: The purpose of this study was to determine the effect of combination sitagliptin with metformin on glycemic control. In addition to, investigation alterations in serum lipids. Materials and Methods: This was a Randomized Controlled Trial involved 85 patients with T2DM at Endocrinology unit, Internal Medicine Department, Tishreen University Hospital, Lattakia, during the period between April 2021-April 2022. Patients were divided into two groups: group 1 received treatment with metformin (44 patients), and group 2 who received sitagliptin with metformin (44 patients). Results: Out of 85 patients, 36 were male and 49 were female, with mean age of the patients was 56.51±9.8. There was no significant difference between two groups regarding of age, gender, and height, whereas body mass index(BMI) was significantly higher in patients who received sitagliptin with metformin. The rate of BMI decreasing was 2.9% in sitagliptin with metformin group versus 1.5% in metformin group without significant difference. HbA1c was decreased significantly in two groups but the higher rate of changes was in combined treatment group (16.6% versus 11.4%), and target HbA1c was obtained in 72.7% of patients in combined treatment group versus 52.3% in metformin group. There was a significant decreasing in fasting and postprandial blood glucose in metformin group; 22.6% and 22.8% and in sitagliptin with metformin group; 32.1% and 36.2% respectively. There was a significant decreasing in triglyceride(TG), total cholesterol(TC), and low density lipoprotein(LDL) in metformin group; 9.7%, 10.3%, and 11.3% versus 13.1%, 13.47%, and 16.1% in sitagliptin with metformin group respectively. High density lipoprotein(HDL) was increased significantly in metformin group (48.95±9.08 after therapy versus 46±8.8 before therapy). Both treatments were well tolerated with mo incidence of hypoglycaemia or abdominal disorders. Conclusion: Initiation of sitagliptin with metformin in patients with T2DM is considered a valuable method in improving glycemic control and serum lipids with reducing the associated morbidity.